Seeing patients : unconscious bias in health care - White, Augustus A., III, 1936-; Chanoff, David (Harvard University Press, 2011)
" ... Use[s] extensive research and interviews with leading physicians to show how subconscious sterotyping influences doctor-patient interactions, diagnosis, and treatment"--Publisher description